1995
DOI: 10.1111/j.1464-410x.1995.tb07714.x
|View full text |Cite
|
Sign up to set email alerts
|

The significance of prostatic intra‐epithelial neoplasia

Abstract: PIN and invasive adenocarcinoma of the prostate were closely associated, and the likelihood for coexistence was higher in patients with high-grade PIN, increasing PSA level or positive findings on TRUS. We recommend that all patients who show high-grade PIN on prostate biopsy be followed very closely with serial PSA measurements and repeat biopsies from both the area of PIN and other areas of the prostate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 15 publications
4
38
1
1
Order By: Relevance
“…Any apparent relation between PIN and elevated serum PSA suggested in some early studies 19±21 may be accounted for by the possibility of concomitant undiagnosed cancer. 15,22 Thus, in a study of 65 radical prostatectomy specimens, high grade PIN was found not to contribute to elevated serum PSA 23 and other recent studies also suggest that PIN alone does not increase the serum PSA. 1,24 We observed similar serum PSA levels in men with benign histological ®ndings and those with high grade PIN, and higher levels in men with cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any apparent relation between PIN and elevated serum PSA suggested in some early studies 19±21 may be accounted for by the possibility of concomitant undiagnosed cancer. 15,22 Thus, in a study of 65 radical prostatectomy specimens, high grade PIN was found not to contribute to elevated serum PSA 23 and other recent studies also suggest that PIN alone does not increase the serum PSA. 1,24 We observed similar serum PSA levels in men with benign histological ®ndings and those with high grade PIN, and higher levels in men with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…14±17 In fact, within all the re-biopsy series summarised in Table 1, the mean or median PSA is greater than 4 ngaml and in four studies it is greater than 8 ngaml. 1,15,17,18 PIN alone probably does not cause raised serum PSA: it is associated primarily with luminal abnormalities with a relatively intact basal cell layer and intact basement membrane. PSA would therefore not be expected to leak excessively into the vascular compartment.…”
Section: Discussionmentioning
confidence: 99%
“…The mean time of follow-up was 17.3 months (range 1-62). The mean number of biopsy sessions was 2.5 (range 2-6), and the median number of biopsy cores was 10 (range [6][7][8][9][10][11][12][13][14].…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14][15] Our aim was to examine our experience with prostatic rebiopsy in patients with HGPIN, ASAP or both.…”
Section: 11mentioning
confidence: 99%
“…The predominately cytoplasmic localization expression of AMACR is consistently up-regulated in prostatic adenocarcinoma and precursor lesion (high-grade prostatic intraepithelial neoplasia-PIN), is absent in the vast majority of benign prostate tissue [27]. High grade PIN in prostate needle biopsy specimen is clinically significant because the risk of carcinoma on biopsy range from 27% to 79% [37]- [44]. AMACR expression can also be identified in prostatic atrophy, atypical adenomatous hyperplasia and benign prostatic glands, and accordingly, a diagnosis of prostatic adenocarcinoma should not be based solely on a positive AMACR immunostain, especially when the luminal staining is weak and/or noncircumferential [30] [33].…”
Section: Introductionmentioning
confidence: 99%